EVALUASI PROGRAM ADIWIYATA DI SMAN 11 SEMARANG - Desy Wahyuningtyas; Priyatno Harsasto (Journal of Politic and Government Studies, 2013)
Adiwiyata this program is one program the Ministry of Environment in orderto promote the creation of knowledge and awareness of the school community inenvironmental protection. The purpose of this program is to create good conditionsfor schools to be places of learning and awareness of the school community. Thisstudy describes the results of an evaluation of the program SMAN11 Adiwiyata inSemarang.The method used in this research using mixed methods (the methods ofqualitative and quantitative methods). Methods of data collection through literaturereview, observation, interviews and documentation, to do with the selection ofquestionnaire respondents using non-probability sampling is random samplingtechnique.Results of this study showed that the program runs fine Adiwiyata in SMAN11 Semarang.Program This gives the change benefits felt by the entire schoolcommunity. It's just for educational and non-educational personnel in carrying outtheir duties on the environment is still lacking. Obstacles in the implementation ofthis program is difficult to invite the school community to keep school.Recommendations for the implementation of the program is to maximizeAdiwiyata participation of educators and non-educators in their duties keeping theschool environment conditions. Moreover communication and socialization betweenBLH with the school and team Adiwiyata in SMAN 11 with the school communityneeds to be improved.Keywords: Evaluation, adiwiyata programs, environmental